2. Informationskompetenztag – unter einem D-A-CH in Bamberg - Martin-Konle, Claudia; Senst, Erik; Schoenbeck, Oliver; Werr, Naoka; Marcus, Schröter (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2018)
Tagungsbericht